Ciência e racionalidade em Thomas Kuhn - Silva, Adan John Gomes da (2013)
The work aims to explore the impact that Thomas Kuhn‟s philosophical work had on the philosophy of science, especially on the common idea of scientific rationality. Besides this, it aims to make clear the position of the author about his understanding of what is to be rational in science. In order to achieve this goal we start giving a panoramic view of the philosophical scientific scene of the first half os the twentieth century, to evince the main character of the concept of rationality more accepted at Kuhn‟s time. In a second moment we show how the ideas of this author contrast with that concept, which gives rise to a series of criticisms of irrationalism. Lastly, we show how Kuhn circumvents these accusations by pointing to a new rationality concept, through which we can conciliate his philosophy with a description of the rational development of science